OPERATIONAL TECHNOLOGY FOR SNOW-COVER MAPPING IN THE CENTRAL ASIAN MOUNTAINS USING NOAA-AVHRR DATA - Qobilov T. (My University, 2001)
An important problem in the evaluation of snow in mountains, is that of the observation and mapping of snow cover variations which is required for snowmelt runoff forecasting in mountain river basins. Satellite data are an efficient tool for these purposes, especially for large and remote river basins. The Snowmelt Runoff Model (SRM) is one of the few snowmelt runoff forecasting models using snow cover information derived from satellite data (or any other remote sensing system). Today, SRM is used operationally in the Main Administration of the Hydro-Meteorological Survey of the Republic of Uzbekistan for forecasting snowmelt runoff in several Central Asian river basins. The Swiss-American SRM is based on the degree-day method and requires daily information on temperature, precipitation and snow-covered areas within several elevation zones. In this context, an extremely important question concerns the accuracy of snow cover classification of satellite data. This paper describes locally developed software tools for increasing the accuracy of snow cover estimation and for operational processing of satellite data.